Evaluating the extent of participation and quality of thinking among pre-service teachers in an asynchronous online discussion environment - Hew, Khe Foon. (2008)
The first purpose of this study was to develop a framework to evaluate the extent of participation and a framework to measure the quality of thinking in an online asynchronous discussion. The second purpose was to use these frameworks to analyse the pre-service teachers’ discussion transcripts.